Expression of CPPED1 in human trophoblasts is associated with timing of term birth. Issue 2 (29th November 2017) - Haapalainen, Antti M.; Karjalainen, Minna K.; Daddali, Ravindra; Ohlmeier, Steffen; Anttonen, Julia; Määttä, Tomi A.; Salminen, Annamari; Mahlman, Mari; Bergmann, Ulrich; Mäkikallio, Kaarin; Ojaniemi, Marja; Hallman, Mikko; et al.
Abstract: Understanding of timing of human parturition is incomplete. Therefore, we carried out proteomic analyses of full‐term placentas from uncomplicated pregnancies to identify protein signatures associated with the onset of spontaneous delivery. We found quantitative associations of 10 proteins with spontaneous term birth, evident either in the basal or in the chorionic plates or in both. Additional 18 proteins were associated according to the location within placenta indicating local variations in protein amounts. Calcineurin‐like phosphoesterase domain‐containing 1 (CPPED1), a phosphatase previously suggested dephosphorylating AKT1/PKB, was one of the identified proteins. qRT‐PCR revealed the mRNA level of CPPED1 was higher in elective caesarean deliveries than in spontaneous births, while immunohistochemistry showed CPPED1 in cytotrophoblasts, syncytiotrophoblasts and extravillous trophoblasts. Noteworthy, phosphorylation status of AKT1 did not differ between placentas from elective caesarean and spontaneous deliveries. Additionally, analyses of samples from infants indicated that single‐nucleotide polymorphisms rs11643593 and rs8048866 of CPPED1 were associated with duration of term pregnancy. Finally, post‐transcriptional silencing of CPPED1 in cultured HTR8/SVneo cells by siRNAs affected gene expression in pathways associated with inflammation and blood vessel development. We postulate that functions regulated by CPPED1 in trophoblasts at choriodecidual interphase have a role in the induction of term labour, but it may be independent of AKT1.